Bi2Se3 nanoplates for contrast-enhanced photoacoustic imaging at 1064 nm. Issue 44 (3rd October 2018) - Park, Sara; Park, Gyeongbae; Kim, Jeesu; Choi, Wonseok; Jeong, Unyong; Kim, Chulhong
Abstract : Bi2 Se3 nanoplates can be a promising PA contrast agent at 1064 nm that offers a high optical absorbance in the second NIR region providing a high contrast imaging and increased depth of penetration. Abstract : Photoacoustic (PA) imaging is a high-resolution biomedical imaging modality, which can be used to visualize biological tissues located beyond the limited penetration depth of existing optical imaging techniques. An optical wavelength of 1064 nm is of great interest in PA imaging due to low intrinsic absorption at this wavelength. Reduced absorption implies an increased depth of imaging, which enables several new clinical applications such as bladder imaging, gastrointestinal (GI) imaging, and sentinel lymph node (SLN) imaging. In addition, a 1064 nm Nd:YAG laser system enables a high power, cost-effective, and compact laser-based PA imaging system. However, at this wavelength, due to low intrinsic contrast, high absorption exogenous PA contrast agents are necessary for imaging. To this end, we present new Bi2 Se3 nanoplates as PA contrast agents at 1064 nm wavelength for PA imaging. We successfully synthesized Bi2 Se3 nanoplates and they exhibited relatively strong PA signals at 1064 nm. We confirmed the increased imaging depth of penetration by imaging the Bi2 Se3 -containing tube located 4.6 cm deep in biological tissues. We present in vivo PA imaging of the bladder, GI tract, and SLN in mice using a Bi2 Se3 contrast agent establishing the clinical feasibility of these agents with a clinical photoacoustic/ultrasound imaging system. Our results confirm that Bi2 Se3 nanoplates are promising PA contrast agents at 1064 nm that offer a high optical absorbance in the second NIR region providing a high contrast imaging and increased depth of penetration.